2007
DOI: 10.1002/masy.200751208
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanical Properties of Chitosan/Poly(Vinyl Alcohol) Blend Films

Abstract: The origins of the thermal and mechanical properties of chitosan and poly(vinyl alcohol) (PVA) with inter-and intra-hydrogen bonds were investigated systematically by using X-ray, DSC, positron annihilation and viscoelastic measurements. Based on their individual properties, the characteristics of the blend films were estimated in relation to their morphology and mechanical properties as a function of chitosan content. The characteristics of the blend films were also analyzed in terms of the deviation from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Overall, the DSC plots of the pure keratin and the blended films correspond to partially crystalline structures. In the DSC curves, the endothermic peak at approximately 140 °C can be attributed to the evaporation of bound water (Te), representing the energy required to vaporize bound water present in the films, followed by another endothermic peak observed at about 220 °C related to the crystalline melting (Tm) of the films, and the peak area representing the crystallinity of the films [9,36]. At a PVA content of 30% in the blended film, the ∆He value for the vaporization of bound water increased from 232.0 to 303.7 J·K −1 (cp.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…Overall, the DSC plots of the pure keratin and the blended films correspond to partially crystalline structures. In the DSC curves, the endothermic peak at approximately 140 °C can be attributed to the evaporation of bound water (Te), representing the energy required to vaporize bound water present in the films, followed by another endothermic peak observed at about 220 °C related to the crystalline melting (Tm) of the films, and the peak area representing the crystallinity of the films [9,36]. At a PVA content of 30% in the blended film, the ∆He value for the vaporization of bound water increased from 232.0 to 303.7 J·K −1 (cp.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…[12,13] One of the hot and also controversial topics about this blend is their miscibility. [14][15][16][17][18][19][20] Strong evidence from some accurate measurements has shown that CS/PVA blend is not fully miscible at molecular level. The miscibility between CS and PVA in the blend was observed to depend on the preparation processing and the relative content of CS and PVA components.…”
Section: Introductionmentioning
confidence: 99%
“…The miscibility between CS and PVA in the blend was observed to depend on the preparation processing and the relative content of CS and PVA components. [11,14,[15][16][17] This special behavior of CS/ PVA blend was partly contributed to the weak intermolecular interaction between PVA and CS because of their tight intramolecular structure. [15] It is well known that the chemical nature of side chains of vinyl polymers usually acts as the main factor in their miscibility behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…20 Cs blended with PVA has been reported to have good mechanical and chemical properties because of the specific intermolecular interactions between PVA and Cs, so this combination is being studied widely in the fields of packaging, membrane filtration, dye adsorption, and biomedicine. [21][22][23] The improved mechanical, ultraviolet-shielding, and antimicrobial properties of PVA/Cs are valuable.…”
mentioning
confidence: 99%